Reporting of violence against children and adolescents in a protective institution in southern Brazil - Priscila Arruda da Silva (Investigación y Educación en Enfermería, 2016)
Objective. This study aimed to analyze the reports of violence against children and adolescents in the period between January 2009 and May 2014 in a municipality protection institution of Rio Grande, RS. Methods. This is a descriptive and documentary study with a quantitative approach that analyzed 800 medical records of Specialized Reference Center for Social Assistance (CREAS), from the development of a research instrument containing the study variables. Results. The results show that 44.5% of the notifications sent to the protection of organs were carried out by family members and evidence of physical signs was the reason that triggered them (34%). The dismissing by abandonment of families is very present in the institution (36.9%), which possibly supports the maintenance of the cycle of violence. Conclusion. The results of this study show that although there were improvements regarding the notification by the family, the number of notifications made by the health and education sectors are still reduced, thereby increasing the need for more effective and articulated actions in these sectors.